ISDS disputes, adjudication and cross-border M&As - Du, Julan; Zhang, Yifei (Journal of Corporate Finance, 2024)
ISDS claims are associated with reductions in the likelihood, frequency, and dollar volume of M&As from claimant home countries to respondent states. The host-state expropriation events underlying ISDS claims show no significant effects. The impact of ISDS claims remains after including traditional country risk metrics. Thus, ISDS claims play a unique role in guiding international investment. They prompt foreign acquirers to adopt risk-avoiding strategies, which affect various deal characteristics. We detect strong substantiation effects of investor-win cases and some acquittal effects of state-win cases. The ISDS claims related to direct expropriations and strong-institution respondent states typically produce more striking effects.